Estimation of Fugitive Dust Levels on A Construction Site Using Digital Image Information - ., Im; Young, Sun; ., Yu; Ho, Jung (International Journal of Engineering and Technology, 2018)
Currently, fugitive dust management on construction sites does not focus on prevention but rather seeks ways to control it after occurrence. In order to effectively manage fugitive dust on a construction site, it is necessary to quantify prevent fugitive dust from occurring, and take immediate measures after occurrence. Therefore, this study proposes a technique to estimate the amount of fugitive dust generated on a construction site using digital image information. Based on the results of this study, it is expected that high levels of fugitive dust on construction sites can be prevented in the future and efficient management will be possible.Â
Keywords: Fugitive Dust; Construction Site; Light Scattering Method; Digital Image Information Analysis Method